2019
DOI: 10.1002/mus.26656
|View full text |Cite
|
Sign up to set email alerts
|

Local FK506 delivery at the direct nerve repair site improves nerve regeneration

Abstract: Introduction The objective of this study is to assess the efficacy of local tacrolimus (FK506) delivery to improve outcomes in the setting of nerve transection injury. Methods FK506 embedded poly(lactide‐co‐caprolactone) films capable of extended, localized release of FK506 were developed. FK506 rate of release testing and bioactivity assay was performed. Mouse sciatic nerve transection and direct repair model was used to evaluate the effect extended, local delivery of FK506 had on nerve regeneration outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Fibrin glue proves its effectiveness in peripheral nerve repair by reducing the inflammatory response and improving axon regeneration. Also, Davis et al showed that the continuous release of local tacrolimus (FK506) to repair site cloud actively inhibits neuroma formation ( 57 ). They used 3D-printing technology to create a polyethylene Y-shape conduit loop, where the nerve will be connected instead of direct connection to autografts.…”
Section: Preventionmentioning
confidence: 99%
“…Fibrin glue proves its effectiveness in peripheral nerve repair by reducing the inflammatory response and improving axon regeneration. Also, Davis et al showed that the continuous release of local tacrolimus (FK506) to repair site cloud actively inhibits neuroma formation ( 57 ). They used 3D-printing technology to create a polyethylene Y-shape conduit loop, where the nerve will be connected instead of direct connection to autografts.…”
Section: Preventionmentioning
confidence: 99%
“…For this reason, systemic administration is not a mainstay in the current treatment of nerve injuries. However, the potential to provide local FK506 via drug‐delivery devices, as well as administration of immunophilin ligands with no immunosuppressive effects, could minimize these concerns while capitalizing on its neuroregenerative effects 15,17–19 . Further, sub‐immunosuppressive doses of FK506 have also shown some beneficial effect in promoting nerve regeneration, 20 although maximum potency is achieved with immunosuppressive doses 21…”
Section: Introductionmentioning
confidence: 99%
“…However, the potential to provide local FK506 via drug-delivery devices, as well as administration of immunophilin ligands with no immunosuppressive effects, could minimize these concerns while capitalizing on its neuroregenerative effects. 15,[17][18][19] Further, sub-immunosuppressive doses of FK506 have also shown some beneficial effect in promoting nerve regeneration, 20 although maximum potency is achieved with immunosuppressive doses. 21 Electrical stimulation (E-stim) is another neuroenhancing therapeutic that has been shown to positively affect nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Many such experimental therapies are growth factors including glial cell line-derived neurotrophic factor (GDNF), fibroblast growth factor (FGF), and brain-derived neurotrophic growth factor ( Fex Svenningsen and Kanje, 1996 ; Lee et al, 2007 ; Gordon, 2009 ). Tacrolimus (FK506), delivered either systemically or locally, has also shown promise in a number of studies ( Konofaos and Terzis, 2013 ; Davis et al, 2019 ; Tajdaran et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%